Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Barito Selatan Tahun 2021: The Effect of the Work Environment on Employee Performance in the Department of Population and Civil Registration in South Barito District, 2021 - Kurniaty, Harlina (Pencerah Publik, 2021)
Work discipline is an important aspect in generating employee performance which will create a conducive work climate so that it can synergize with increasing employee morale or enthusiasm to achieve a goal. This study aims to see the effect of work influence on employee performance at the Manpower and Transmigration Office of South Barito Regency in 2021. In this study, the author of quantitative quantitative research. The data used are primary and secondary data collected through, observation, interviews, documentation and questionnaires. The sample used as the object of research was 30 people. This study has two variables, namely the independent (X) Work Discipline and the dependent variable (Y) Employee Performance in the job training and workforce placement sections. The results obtained in the calculation of simple linear regression are Y = 18,628 + 0.553 x where the value (a) is 18,628; and the coefficient value (b) is 0.553. Then the results of tcount> are obtained from the test that tcount> ttable (3.374 ≥ t table 2.051) then Ho is rejected and Ha is accepted, meaning that there is an effect of work discipline on employee performance at the Manpower and Transmigration Office of South Barito Regency in 2021. Based on the conclusion, it can be seen that the effect of work discipline on employee performance in the job training section and placement of workers at the Manpower and Transmigration Office of South Barito Regency in 2021 is important because it can improve employee performance in carrying out their duties according to des jobs.